Regional Grouping Based on Cubic Water Using K-Means Algorithm at Perumda Air Minum Tirta Silaupiasa Asahan Regency - Munawar, Fajar; Nasution, Akmal; Santoso, Santoso (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Perumda Air Minum Tirta Silaupiasa Asahan Regency is a regional company that has the authority to provide clean water consumption needs for the community in Asahan Regency. Currently, clean water needs, especially for households and industries in Asahan Regency, are supplied by Perumda Air Minum Tirta Silaupiasa which is located at Jalan Jend. Ahmad Yani No. 33, Kisaran, Sei Renggas, West Kisaran, Sei Renggas, West Kisaran City District, Asahan Regency, North Sumatra 21213. Currently, the need for clean water for the people of Asahan Regency comes from Perumda Air Minum Tirta Silaupiasa Asahan Regency. However, the amount of clean water provided for people living in areas with high cubic water in Asahan Regency is still relatively small, this is because the Perumda Air Minum Tirta Silaupiasa Asahan Regency does not know which areas have high, medium and low cubic water usage. Therefore, Perumda Air Minum Tirta Silaupiasa Asahan Regency needs to follow up on this problem by grouping areas based on water cubic. To manage the data, a technique is needed that can be used to extract information from the data, the technique is Data Mining. The purpose of this system is to find out how to analyze water cubic data using the K-Means Algorithm and design a website-based system with the PHP programming language and MySQL Database to determine areas with high, medium, and low water cubic. K-means clustering is a data analysis method or data mining method that performs unsupervised modeling and is one of the data clustering methods using a partition system. The data obtained in the recap of cubic water data at Perumda Air Minum Tirta Silaupiasa Asahan Regency for the period 2021-2023. The research method used in this research is quantitative research method. From the results of implementation and testing the results of the calculation of the K-means clustering method are the results of clustering cubic water in the Asahan district area with high water cubic including West Kisaran with a minimum value of 101727.9655 and East Kisaran with a minimum value of 101727.9655. Then in the Asahan district area with medium water cubic including Air Joman with a minimum value of 151144.2025 and Simpang Empat with a minimum value of 151144.2025. Then in the Asahan district area with low water cubic including B.P Mandoge with a minimum value of 66801.4373, Buntu Pane with a minimum value of 105608.8293, Desa Gajah with a value of 59925.2623, Lubuk Palas with a value of 75832.9197, Meranti with a value of 2892.8137, Sei Kamah II with a value of 47997.2206, and Sei Kepayang Barat with a value of 197781.2457.